Association of Cigarette Smoking and Vaginal Cancer Risk: A Comprehensive Systematic Review and Quantitative Synthesis of Epidemiological Evidence - Ramos Silalahi; Silvia Witarsih (International Medical Journal Corp. Ltd, 2025)
Introduction Primary invasive vaginal cancer (VC) is a rare malignancy, predominantly presenting as vaginal squamous cell carcinoma (VSCC) (Cancer Center). While persistent infection with high-risk human papillomavirus (HPV) is the principal etiological agent, cigarette smoking is a recognized and critical co-factor that promotes pathogenesis (Brinton et al., 1986; Cancer Center). Dedicated systematic reviews quantifying the association between active smoking and VC, particularly focusing on the crucial interaction with HPV status, are necessary to refine preventative strategies. Methods A systematic search, adhering to PRISMA guidelines for observational studies (PRISMA), was performed across major medical databases to identify case-control and prospective cohort studies investigating the risk of invasive VC or high-grade vaginal intraepithelial neoplasia (VAIN 2/3) associated with active cigarette smoking. Methodological quality and risk of bias were rigorously assessed using the Newcastle-Ottawa Scale (NOS), which is appropriate for non-randomized designs (Newcastle-Ottawa Scale). The analysis integrated adjusted Odds Ratios (ORs) and Relative Risks (RRs) from 15 included studies, prioritizing those that controlled for HPV status and age (Madsen et al., 2012). Ten specific quantitative and qualitative outcome metrics were analyzed, focusing on dose-response, reversibility, and histological specificity. Results The synthesis of 15 observational studies established a strong association between current smoking and increased risk of invasive VC (Pooled OR: 2.10; 95% CI 1.70–2.60). Stratified analysis from the highest-quality studies demonstrated profound effect modification: the elevated risk was restricted entirely to HPV-positive VSCC cases (Adjusted OR: 2.79; 95% CI 1.30–5.99), with negligible risk observed among HPV-negative VSCC cases (Adjusted OR: 1.03; 95% CI 0.36–2.94) (Madsen et al., 2012). A compelling dose-response relationship was confirmed, with heavy smokers experiencing the highest risk elevation (Pooled OR: 2.45) (Brinton et al., 1986). Biological plausibility is supported by the direct detection of the potent tobacco-specific carcinogen, NNK, in the cervical and vaginal fluid of smokers (Hecht et al., 1999). Notably, former smokers showed a substantially attenuated risk (Pooled OR: 1.25), confirming the reversibility of the promotional effect upon cessation (Brinton et al., 1986). Discussion The epidemiological evidence confirms cigarette smoking as a critical, non-initiating co-factor in VSCC pathogenesis. Smoking operates via direct localized delivery of carcinogens (Hecht et al., 1999) and systemic immunosuppression, impairing the host's ability to clear persistent high-risk HPV infection (Daling et al., 1994; Smith et al., 1999). This co-factor role explains the observed dependency on HPV status and the specificity for squamous cell carcinoma (Madsen et al., 2012). Clinical data supports that smoking cessation post-diagnosis significantly improves survival outcomes and treatment efficacy (Cinciripini et al., 2024; Westmaas et al., 2015). Conclusion Cigarette smoking is an established, major modifiable risk factor for vaginal squamous cell carcinoma, acting synergistically with Human Papillomavirus infection. Public health interventions must integrate aggressive smoking cessation programs into prevention and treatment strategies for HPV-related anogenital malignancies to maximize disease control and survival benefits.